Plant Life in Extreme Environments: How Do You Improve Drought Tolerance? - Bechtold, Ulrike (Frontiers in Plant Science, 2018)
Systems studies of drought stress in resurrection plants and other xerophytes are rapidly identifying a large number of genes, proteins and metabolites that respond to severe drought stress or desiccation. This has provided insight into drought resistance mechanisms, which allow xerophytes to persist under such extreme environmental conditions. Some of the mechanisms that ensure cellular protection during severe dehydration appear to be unique to desert species, while many other stress signaling pathways are in common with well-studied model and crop species. However, despite the identification of many desiccation inducible genes, there are few “gene-to-field” examples that have led to improved drought tolerance and yield stability derived from resurrection plants, and only few examples have emerged from model species. This has led to many critical reviews on the merit of the experimental approaches and the type of plants used to study drought resistance mechanisms. This article discusses the long-standing arguments between the ecophysiology and molecular biology communities, on how to “drought-proof” future crop varieties. It concludes that a more positive and inclusive dialogue between the different disciplines is needed, to allow us to move forward in a much more constructive way.